Ciprofloxacin Concentrations 100-Fold Lower than the MIC Can Select for Ciprofloxacin Resistance in Neisseria subflava: An In Vitro Study - Zina Gestels; Saïd Abdellati; Chris Kenyon; Sheeba Santhini Manoharan-Basil (MDPI AG, 2024)
Neisseria gonorrhoeae can acquire antimicrobial resistance (AMR) through horizontal gene transfer (HGT) from other Neisseria spp. such as commensals like Neisseria subflava. Low doses of antimicrobials in food could select for AMR in N. subflava, which could then be transferred to N. gonorrhoeae. In this study, we aimed to determine the lowest concentration of ciprofloxacin that can induce ciprofloxacin resistance (minimum selection concentration-MSC) in a N. subflava isolate (ID-Co000790/2, a clinical isolate collected from a previous community study conducted at ITM). In this study, Neisseria subflava was serially passaged on gonococcal (GC) medium agar plates containing ciprofloxacin concentrations ranging from 1:100 to 1:10,000 below its ciprofloxacin MIC (0.006 µg/mL) for 6 days. After 6 days of serial passaging at ciprofloxacin concentrations of 1/100th of the MIC, 24 colonies emerged on the plate containing 0.06 µg/mL ciprofloxacin, which corresponds to the EUCAST breakpoint for N. gonorrhoeae. Their ciprofloxacin MICs were between 0.19 to 0.25 µg/mL, and whole genome sequencing revealed a missense mutation T91I in the gyrA gene, which has previously been found to cause reduced susceptibility to fluoroquinolones. The N. subflava MSCde novo was determined to be 0.06 ng/mL (0.00006 µg/mL), which is 100×-fold lower than the ciprofloxacin MIC. The implications of this finding are that the low concentrations of fluoroquinolones found in certain environmental samples, such as soil, river water, and even the food we eat, may be able to select for ciprofloxacin resistance in N. subflava.